(untitled) (Malaysian Management Journal, 2019)
Junk food has been making fast inroads in Indian market. Socio-culturally India has been a collectivist and tradition dominated society, where the concept of food is very different from junk food. This study aims to explore the rising incidence of junk food based on the theory of planned behavior and contributes to understanding the consumption drivers for possible social marketing implications. The findings suggest that out of the three constructs: attitude, social norms and perceived behavioral control, only perceived behavioral control was found to be the significant determinant of intentions. The study has implications for social marketers. For controlling the rising incidence of junk food, the strategy should focus on developing a sense of perceived control. This requires building self-belief and increasing barriers to access of junk food. This paper contributes to the body of literature in understanding consumption drivers of junk food, particularly in a collectivist and family oriented society like India and how efforts to control rising incidence of junk food can be made more effective.